Advances in library administration and organization. Vol. 18 - Williams, Delmus Eugene; Garten, Edward D. (Advances in library administration and organization, 2001)
This monograph offers writing that is both professional and academic. Volume 18 continues to be characterized by a focused eclecticism, informed by theory and reflection, and stretching the boundaries of practice. Among the 11 contributions here are forward-thinking pieces on professional stress resulting from the impact of virtual libraries, an integrated approach to the development of an information resources strategic plan, an international perspective on quality assurance in library support of distance learning, and a research study that offers a methodology to determine and measure gender-based salary disparities in academic libraries. Additionally, this volume includes papers presented at a symposium at the University of Michigan in honour of the career of Richard Dougherty, one of America's most well-regarded library administrators. These papers note some of the obstacles and challenges that those working in today's academic libraries face in their attempts to clear the way for fresh visions of library leadership suited for the years ahead.